2016
DOI: 10.1021/jacs.6b05627
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Fission via an Excimer-Like Intermediate in 3,6-Bis(thiophen-2-yl)diketopyrrolopyrrole Derivatives

Abstract: Singlet fission (SF) in polycrystalline thin films of four 3,6-bis(thiophen-2-yl)diketopyrrolopyrrole (TDPP) chromophores with methyl (Me), n-hexyl (C6), triethylene glycol (TEG), and 2-ethylhexyl (EH) substituents at the 2,5-positions is found to involve an intermediate excimer-like state. The four different substituents yield four distinct intermolecular packing geometries, resulting in variable intermolecular charge transfer (CT) interactions in the solid. SF from the excimer state of Me, C6, TEG, and EH ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
291
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(316 citation statements)
references
References 93 publications
25
291
0
Order By: Relevance
“…[3][4][5][6][7] On the other hand it has been recently found that excimer formation can also have a positive effect on the properties of organic materials, facilitating processes such as singlet fission. [8][9][10][11][12] For this reason, the understanding of the excimer formation dynamics in molecular aggregates is of fundamental importance for the development of novel materials that can be employed in organic electronics or photovoltaics applications. In addition to their importance for the development of functional materials, excimers can be also employed as probes in biological molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] On the other hand it has been recently found that excimer formation can also have a positive effect on the properties of organic materials, facilitating processes such as singlet fission. [8][9][10][11][12] For this reason, the understanding of the excimer formation dynamics in molecular aggregates is of fundamental importance for the development of novel materials that can be employed in organic electronics or photovoltaics applications. In addition to their importance for the development of functional materials, excimers can be also employed as probes in biological molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The development of solution-processable OFETs has attracted great interest because of its cost-effective and low-energy consumption processes. [9,10] www.advelectronicmat.de gold-based p-type OFETs would perform much better than goldbased n-type OFETs, for example, having high mobility values, due to relatively small energy barriers between Au and p-type active layer. OFETs based on p-type organic semiconductors and gold source/drain electrodes achieved much progress during the last two decades.…”
mentioning
confidence: 99%
“…HBC is a polycyclic aromatic hydrocarbon made up of thirteen fused six membered rings, which forms a mesophase. [6,37] Their studies on substituent variation in crystalline diketopyrrolopyrroles demonstrated that the torsion induced on substitution of thienyl (TDPP) by phenyl (PDPP) is sufficient to increase the π-π stacking distance and completely shut down SF, so SF in DPP is very sensitive to local-order (intermolecular coupling), which is not ideal for inclusion in OPV devices. [35] The HBC core shows strong π−π intermolecular association and can show high charge mobilities (≈1 cm 2 V −1 s −1 in certain silyl-substituted HBCs using pulse-radiolysis time resolved microwave conductivity measurements).…”
mentioning
confidence: 99%
“…Soluble HBC derivatives show strong self-association in solution and discotic columnar structures with ordered morphology in films. [37] Our interest in developing solution processable SF materials for use for printed organic solar cells, led us to question, can we use the liquid crystallinity inherent in FHBC as a self-organizing motif and scaffold to pre-organize the DPP chromophore to promote intramole cular SF in amorphous thin films? [36] Substitution of HBC with 9,9-dioctylfluorene (FHBC) imparts solubility and the ability to form mixtures with other conjugated molecules.…”
mentioning
confidence: 99%